Digital Publik Relation KEMENSOS dalam Pemanfataan Sosial Media - Hildawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the rapidly developing digital era, social media has become a highly effective communication tool for various organizations, including government institutions. This study aims to analyze the digital public relations (PR) strategies of the Indonesian Ministry of Social Affairs (Kemensos) in utilizing social media, as well as to evaluate the effectiveness and challenges faced. This research employs a qualitative method with a case study approach. Data were collected through content analysis of Kemensos' social media, in-depth interviews with Kemensos officials and digital communication experts, and online surveys of the public to evaluate their perceptions and engagement with Kemensos' social media content. The results show that Kemensos implements various digital PR strategies to increase public awareness and participation in social programs. The published content includes information on social programs, education, and important announcements, presented in various formats such as text, images, and videos. However, Kemensos faces several challenges, such as crisis management and reputation management on social media.This study finds that Kemensos' use of social media significantly influences the public's image and trust in the institution. The level of public engagement with Kemensos' content is also quite high, indicating the effectiveness of the implemented digital communication strategies. However, there is a need to improve responsiveness and crisis management in dealing with issues that arise on social media. Based on these findings, this study provides practical recommendations for Kemensos to enhance their digital PR strategies, including improving content quality, better crisis management, and increasing public engagement. This research also contributes to the development of digital public relations strategies in other government institutions, providing insights for academics and communication practitioners.